A Patient with Milky Urine: Nonparasitic Chyluria and Silver Nitrate Sclerotherapy. (23rd July 2020) - Sivashankar, M.; Nandasena, A. C. N.
Abstract : Chyluria has become a rare clinical presentation in Sri Lanka, which may have a direct correlation with the low prevalence of lymphatic filariasis following the use of diethylcarbamazine and albendazole mass drug administration (MDA) for five rounds between 2002 and 2006. Here we report a 50-year-old male who presented with milky urine and progressive weight loss, diagnosed as having nonparasitic chyluria. The patient was initially managed with a trail of diethylcarbamazine (DEC) 6 mg/kg/day for 21 days and a low-fat diet with an unsatisfactory response. Subsequent management with endoscopic instillation of 0.5% silver nitrate brought in him a quick response, which was maintained for a year. Endoscopic sclerotherapy is considered a safer, effective and a minimally invasive treatment option for symptomatic patients.